Kecelakaan Kerja pada Perusahaan Konstruksi: Sebuah Telaah Literatur - Syafiq, Umar; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this conceptual research is to present the current literature review related to Causes of Occupational Accidents in Construction Companies. Construction companies are currently the most significant contributor to the number of occupational accidents in Indonesia. In fact, there are already specific safety K3 guidelines for construction companies that should be the handle of construction companies to reduce the number of work accidents. Various kinds of literature related to the causes of occupational accidents at construction companies are discussed in this study, along with the upcoming research agenda related to change management.